UNCERTAINTY AND BANK FUNDING LIQUIDITY RISK IN VIETNAM - Dan Dang, Van; Chung Nguyen, Hoang (Economic Annals, 2022)
This paper examines the impact of uncertainty on bank funding liquidity risk. Based on a sample of Vietnamese commercial banks from 2007 to 2019, we show evidence that micro uncertainty in the banking sector leads to higher funding liquidity risk, as proxied by lower deposit ratios. Additional analyses reveal that this nexus widely depends on bank heterogeneity. More precisely, various bank-specific forces that improve banks’ financial strength (i.e., an increase in bank return, loan quality, capitalization, liquid assets, and bank size) tend to mitigate the adverse impact of uncertainty on bank funding liquidity risk. Our findings are robust to changes in multiple combinations of regressors, different key bank-level variables to calculate the dispersion of shocks as banking uncertainty measures, and alternative econometric approaches.